Optimization and sustainability assessment of a continuous flow Ru-catalyzed ester hydrogenation for an important precursor of a β2-adrenergic receptor agonist. Issue 17 (18th August 2020) - Prieschl, Michael; García-Lacuna, Jorge; Munday, Rachel; Leslie, Kevin; O'Kearney-McMullan, Anne; Hone, Christopher A.; Kappe, C. Oliver
Abstract : The development of a continuous flow ruthenium-catalyzed ester reduction using hydrogen gas is described. The assessment of green metrics show the protocol is substantially more sustainable than commonly employed metal hydride reductions. Abstract : The development of a ruthenium-catalyzed continuous flow ester hydrogenation using hydrogen (H2 ) gas is reported. The reaction was utilized for the reduction of an important precursor in the synthesis of abediterol, a β2 -adrenoceptor agonist that has undergone phase IIa clinical trials for the treatment of asthma and chronic obstructive pulmonary disorder. The reaction was investigated within a batch autoclave by using a design of experiments (DoE) approach to identify important parameter effects. The optimized flow process was successfully operated over 6 h with inline benchtop 19 F NMR spectroscopy for reaction monitoring. The protocol is shown to be high yielding (98% yield, 3.7 g h −1 ) with very low catalyst loading (0.065 mol%). The environmental impact of the Ru-catalyzed hydrogenation was assessed and compared to an existing stoichiometric lithium aluminum hydride (LAH) reduction and sodium borohydride (NaBH4 ) reduction. The process mass intensity (PMI) for the Ru-catalyzed hydrogenation (14) compared favorably to a LAH reduction (52) and NaBH4 reduction (133).